Abstract Cinema and Aesthetic Utopia in the Interwar Period. - RUSU, CRISTIAN (Caietele Echinox, 2015)
The article attempts to clarify the positioning and the status of abstract cinema of the 1920s and the 1930s within the broader category of experimental cinema, and it does so through an analysis of the artistic context in which it emerged and of its visual language. The abstract cinema, or absolute cinema, as it was called by those designing it, much unlike the experimental films made during that time, employs an iconoclastic language. Another topic of debate I propose is whether abstract cinema can generate a specific imaginary, given that cinema is, by definition, a story projected onto a screen, in itself a generator of a parallel time for the viewers, where they can build an imaginary. Was this a utopian endeavor or not?